Characterization of a new bacillus cereus ATUAVP1846 strain producing penicillin V acylase, and optimization of fermentation parameters - Sunder, Avinash Vellore; Kumar, Atul; Naik, Neha; Pundle, Archana V. (Annals of Microbiology, 2012)
Penicillin acylases are involved chiefly in the industrial production of semisynthetic penicillins, which remain the most widely used group of antibiotics. We have isolated a new bacterial strain ATUAVP1846 that produces penicillin V acylase (PVA). Phylogenetic analysis using 16S rRNA sequencing showed 99.37% homology with Bacillus cereus. Maximum PVA production was observed with B. cereus ATUAVP1846 at 30A degrees C, pH 7 after 24 h fermentation time under submerged conditions. Highest enzyme productivity was achieved using sucrose as carbon source, and tryptone and ammonium hydrogen phosphate as nitrogen sources. Minimal medium containing 0.4% glucose and 0.3% ammonium hydrogen phosphate was found to be optimal for maximum PVA production from B. cereus ATUAVP1846. The crude enzyme from B. cereus ATUAVP1846 was partially purified using ammonium sulfate fractionation and showed highest enzymatic activity in the hydrolysis of penicillin V at 40A degrees C and pH 6. The crude enzyme preparation also showed unique substrate specificity, preferring ampicillin and cephalexin over penicillin V.
Keywords: 16S rRNA; Bacillus cereus; isolation; Ntn hydrolase; Optimization; Penicillin acylase

Purification and characterization of YxeI, a penicillin acylase from Bacillus subtilis - Rathinaswamy, Priya; Gaikwad, Sushama M.; Suresh, C. G.; Prabhune, Asmita; Brannigan, James A.; Dodson, Guy G.; Pundle, Archana V. (International Journal of Biological Macromolecules, 2012)
The paper reports the purification and characterization of the first penicillin acylase from Bacillus subtilis. YxeI, the protein annotated as hypothetical, coded by the gene yxeI in the open reading frame between iol and hut operons in B. subtilis was cloned and expressed in Eshcherichia coli, purified and characterized. The purified protein showed measurable penicillin acylase activity with penicillin V. The enzyme was a homotetramer of 148 kDa. The apparent Km of the enzyme for penicillin V and the synthetic substrate 2-nitro-5-(phenoxyacetamido)-benzoic acid was 40 mM and 0.63 mM, respectively, and the association constants were 8.93 x 10(2) M-1 and 2.51 x 10(5) M-1, respectively. It was inhibited by cephalosporins and conjugated bile salts, substrates of the closely related bile acid hydrolases. It had good sequence homology with other penicillin V acylases and conjugated bile acid hydrolases, members of the Ntn hydrolase family. The N-terminal nucleophile was a cysteine which is revealed by a simple removal of N-formyl-methionine. The activity of the protein was affected by high temperature, acidic pH and the presence of the denaturant guanidine hydrochloride. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bacillus subtilis; Conjugated bile acid hydrolases; Ntn hydrolase; Penicillin acylase